The Representation of Protest of Lower Socioeconomic Class Javanese People In Tiwiek S.A.’S Carang-Carang Garing - Andayani, Ambar; Rudi Supsiadji, Mateus; Jupriono, Jupriono (International Journal of Educational Research & Social Sciences, 2025)
Javanese literature can be categorized as modern literature with genres of novel, novella, drama and short story although researchers have not yet discussed Javanese literature in the same stage as Western literature. This paper analyses Tiwiek Suwignyo Adi’s Carang-carang Garing by using theory of literary anthropology. Literary anthropology is a study that combines literary studies with anthropology, focusing on the relationship between literary works and their social, cultural, and historical contexts. Begin with narrating the morning life of a lower economic class Javanese family, Adi’s Carang-carang Garing tells in a close and detail way about the struggle of lower economic class Javanese mpeople in facing the capitalist industry as the circumstance of Indonesian society in the 20th century. In this case what is faced by the main characters, Suyatman and Darmini is situation where there is a violation which breaks the harmony of Javanese society, Bambang does not want to admit his deed in impregnating Darmini and Suyatman feels jealous to his sister’s family who always get riches in their life. Darmini kills Bambang and Suyatman kills his sister’s son. Their evil to kill is not just a protest between members of Javanese people, as part of hierarchical order in Javanese society the protest is also the symbol of protest from lower economic class to the ruler who does not care to the lower economic class people.